The Influence of Creativity and Innovative Behavior on Employee Performance at Warung Muncang Puppet Center Bandung - Bagja, Hafied Noor; Hadi, Adwi Mulyana (Universitas Pamulang, 2023)
Economic growth in Indonesia from year to year is increasingly showing a positive direction. This development has driven the business world, one of which is the emergence of small and medium-sized industries. So to support the development of the industry, business people who have creativity and innovative behavior are needed to do various ways in order to compete and be able to meet changing market needs. This study aims to determine how the influence of creativity and innovative behavior on employee performance at the Warung Muncang Puppet Center Bandung. The methodology that the author uses is descriptive and verification method with the population taken for this research is 32 business people employees and at the same time become the research sample. While the analytical method used in this study is multiple linear regression analysis at a significance level of 5%. The program used in analyzing the data uses the Statistical Package for Social Sciences (SPSS) Ver.27.00. The results showed that there was an influence of creativity and innovative behavior on employee performance at the Warung Muncang Puppet Center Bandung. Creativity and innovative behavior can contribute to employee performance by 77.3%.